2021
DOI: 10.3389/fmicb.2021.733441
|View full text |Cite
|
Sign up to set email alerts
|

The Trp-rich Antimicrobial Amphiphiles With Intramolecular Aromatic Interactions for the Treatment of Bacterial Infection

Abstract: Antibiotic resistance is emerging as a hot issue with the abuse and overuse of antibiotics, and the shortage of effective antimicrobial agents against multidrug resistant bacteria creates a huge problem to treat the threatening nosocomial skin and soft tissue infection. Antimicrobial peptides (AMPs) exhibite enormous potential as one of the most promising candidates of antibiotic to fight against pathogenic infections because of its unique membrane penetration mechanism to kill pathogens, whereas the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Recently, Wang and coworkers designed a series of Trp-rich peptides based on the template (VKKX)4, to obtain paired Trp at the i and i + 4 position on the backbone of peptides (where X is W , A , or L ), and to study the effect of intramolecular aromatic interactions on the bioactivity of these AMPs (Wang et al ., 2021). The peptides contain either 2 Trp, (VKKWVKKAVKKWVKKA; VKKWVKKWVKKAVKKA), 3 Trp (VKKWVKKWVKKAVKKW; VKKWVKKWVKKWVKKA), or 4 Trp, (VKKWVKKWVKKWVKKW).…”
Section: Trp-containing Amps and Glycoconjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang and coworkers designed a series of Trp-rich peptides based on the template (VKKX)4, to obtain paired Trp at the i and i + 4 position on the backbone of peptides (where X is W , A , or L ), and to study the effect of intramolecular aromatic interactions on the bioactivity of these AMPs (Wang et al ., 2021). The peptides contain either 2 Trp, (VKKWVKKAVKKWVKKA; VKKWVKKWVKKAVKKA), 3 Trp (VKKWVKKWVKKAVKKW; VKKWVKKWVKKWVKKA), or 4 Trp, (VKKWVKKWVKKWVKKW).…”
Section: Trp-containing Amps and Glycoconjugatesmentioning
confidence: 99%
“…In another study, it was found again that Arg- and Trp-rich sequences (H-RRWTWWWTWRR-NH 2 and H-RRWSWWWSWRR-NH 2 ) have a broad spectrum of antimicrobial activity against Gram-negative and Gram-positive bacteria (Wang et al ., 2021). Regarding their interactions with cell wall components, the two peptides interact with both LPS and LTA, although their affinity seems to be lower than melittin.…”
Section: Trp-containing Amps and Glycoconjugatesmentioning
confidence: 99%
“…The cytoplasmic membrane depolarization assays were performed with the membrane potential-sensitive fluorescent dye 3,3′-dipropylthiadicarbocyanine (diSC3-5). The testing procedure is the same as described in our previous reports (Wang Z. et al, 2021). We would not go into detail here in order to avoid repetition as much as possible.…”
Section: Cytoplasmic Membrane Permeability and Depolarization Assaysmentioning
confidence: 99%
“…Despite the fact that AMPs have shown a promising future in overcoming antibiotic resistance, several obstacles, such as insufficient bioactivities, high toxicity, susceptibility to protease degradation, and high production costs, continue to impede AMPs' further development as commercially available drugs. Numerous strategies have been suggested to increase the antimicrobial potency and lessen the toxicity of AMPs, including template modification, minimalist de novo design, and designbased AMP libraries (Ong et al, 2014;Tan et al, 2020;Yang et al, 2020;Li et al, 2021;Wang C. et al, 2021;Wang Z. et al, 2021). Moreover, a variety of strategies have been investigated to increase the proteolytic stability of AMPs, including sequence changes, peptidomimetics, cyclization, N-methylation, PEGylation, lipidation, and glycosylation (Lai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Trp with unique physicochemical properties is desired for insertion into the cell membrane. [12,13] The simultaneous usage of Trp and cationic residues has been successfully used in designing AMPs, [10,14,15] in which cation-π and Trp-Trp interactions can have a significant role in their structural stability. [16,17] Plicatamide (FFHLHFH-deΔDOPA) is a short natural AMP isolated from the blood cells of Styela plicata.…”
Section: Introductionmentioning
confidence: 99%